Liberal socialism : an alternative social ideal grounded in Rawls and Marx - Hunt, Ian (Lexington Books, 2015)
Liberal Socialism exposes false ideas of justice behind neo-liberal capitalism and combines Rawls' ideas on justice and Marx's views on capitalism to make a plausible case for the alternative social ideal of liberal socialism. A fixed social structure gives equal weight to all competing claims for rights, liberties, and shares of the burdens and benefits of social cooperation, while allowing a democratic majority vote for liberal socialism.
Keywords: Rawls, John, -- 1921-2002.; Marx, Karl, -- 1818-1883.; Marx, Karl, -- 1818-1883; Rawls, John, -- 1921-2002; Socialism -- Philosophy.; Social justice -- Philosophy.; Justice sociale -- Philosophie.; POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism.; Social justice -- Philosophy; Socialism -- Philosophy